Analyzing the immunogenicity of bivalent booster vaccinations in healthcare workers: The SWITCH ON trial protocol - Tan, Ngoc H.; Sablerolles, Roos S. G.; Rietdijk, Wim J. R.; Goorhuis, Abraham; Postma, Douwe F.; Visser, Leo G.; Bogers, Susanne; Geers, Daryl; Zaeck, Luca M.; Koopmans, Marion P. G.; Dalm, Virgil A. S. H.; Kootstra, Neeltje A.; et al. (Frontiers in Immunology, 2022)
Vaccination against coronavirus disease 2019 (COVID-19) has contributed greatly to providing protection against severe disease, thereby reducing hospital admissions and deaths. Several studies have reported reduction in vaccine effectiveness over time against the Omicron sub-lineages. However, the willingness to receive regular booster doses in the general population is declining. To determine the need for repeated booster vaccinations in healthy individuals and to aid policymakers in future public health interventions for COVID-19, we aim to gain insight into the immunogenicity of the additional bivalent booster vaccination in a representative sample of the healthy Dutch population. The SWITCH ON study was initiated to investigate three main topics: i) immunogenicity of bivalent vaccines after priming with adenovirus- or mRNA-based vaccines, ii) immunological recall responses and reactivity with relevant variants after booster vaccination, and iii) the necessity of booster vaccinations for the healthy population in the future.